Phytochemicals and protective effects of Moringa oleifera seed extract on CCl4- induced hepatotoxicity and hemotoxicity in rats - Biomy, Eman S. S.; El-Sayed, Mossad G. A.; El-Komy, Ashraf A. A. (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Moringa oleifera is high valued plant and used in many countries around the world. The seed of Moringa oleifera (MO) is an important part and has a remarkable medicinal, nutritional and socio-economic values, this study, therefore, was designed to clarify the protective effect of Moringa oleifera hydroethanolic seed extract (MOSE) against carbon tetrachloride (CCl4) induced hepatoxicity and hemotoxicity in rats. Methods: A total of one hundred and five male rats were randomly divided into 7 groups of 15 rats each. The hydroethanolic seed extract (30%) was administered orally for one month at 250 and 500mg/kg body weight. Samples were collected after day1,15 and 30 post administration. Results: Phytochemical, biochemical, hematological and hisopathological examinations were utilized to investigate hepatoprotective activity of MOSE. The results obtained demonstrated that, phytochemicals such as alkaloids, glycosides, anthraquinones, tannins, flavonoids, gum, resin, saponins, terponoids, protein and fats were detected in the seeds. Treatment with the MOSE caused a significant (P<0.05) decrease in the activities of aspartate aminotransferase (AST), alanine aminotransferase (ALT), total bilirubin, triglyceride and lipid peroxidation (MDA), while total protein and albumin level significantly (P<0.05) increased compared to CCl4 group. Also, treatment with the MOSE showed a significant (P<0.05) increase Hb content and RBCs, whereas WBCs and lymphocyte count significantly (P<0.05) decreased throughout the period of administration when compared to the rats in CCl4 group. The results obtained were comparable to silymarin. Histopathological examination of liver tissues confirmed the biochemical data. Conclusions: It could be concluded that, CCl4 induced hepatotoxicity and hemotoxicity is ameliorated by MOSE especially in high dose of (500mg/kg). This effect is attributed to free radical scavenging activity and potent antioxidant activity of its components (Flavonoid, tannin, alkaloid and saponin).